Enhanced training protects memory against amnesia produced by concurrent inactivation of amygdala and striatum, amygdala and substantia nigra, or striatum and substantia nigra - Salado-Castillo, Rigoberto; Sánchez-Alavez, Manuel; Quirarte, Gina L.; Martínez García, María I.; Prado-Alcalá, Roberto A. (Frontiers in Behavioral Neuroscience, 2011)
Memory is markedly impaired when normal activity of any of a number of cerebral structures is disturbed after a learning experience. A growing body of evidence indicates, however, that such interference with neuronal function becomes negligible when the learning experience is significantly enhanced. We now report on the effects of enhanced training on retention after temporary inactivation of cerebral nuclei known to be involved in memory, namely the substantia nigra (SN), striatum (STR), and amygdala (AMY). When training was conducted with a relatively low intensity of footshock (1.0 mA), post-training infusion of lidocaine into the SN, DS, or AM produced a marked memory deficit. Increasing the aversive stimulation to 2.0 mA protected memory from the amnesic effect of intranigral lidocaine, but there was still a deficit after its infusion into the STR and AMY. Administration of lidocaine into each of these nuclei, in the groups that had been trained with 3.0 mA, was completely ineffective in producing alterations in memory consolidation. Simultaneous infusion of lidocaine into STR+SN, AMY+SN, or AMY+STR was also ineffective in altering memory formation when the highest footshock intensity was used for training. To our knowledge, this is the first demonstration that an enhanced learning experience guards against memory deficits after simultaneous temporary interruption of neural activity of brain nuclei heretofore thought to be necessary for memory formation. These findings support the proposition that brain structures involved in memory processing are functionally connected in series during memory consolidation and that, after an enhanced learning experience, these structures become functionally connected in parallel.